Indoor Tanning within UK Young Adults: An Extended Theory of Planned Behaviour Approach. (17th September 2012) - Dodd, Lorna J.; Forshaw, Mark J.; Williams, Stella
Abstract : The indoor tanning industry poses a long-term public health risk. Despite the adverse health effects, indoor tanning seems to be gaining considerable popularity. The study examined indoor tanning intentions and behaviour within UK young adults using an extended theory of planned behaviour model, which included variables on "appearance reasons to tan, " "perceived susceptibility to damaging appearance, " "perceived susceptibility to health consequences, " and "tanning knowledge." The model was successful in predicting indoor tanning intentions and behaviour (explained 17% and 71%, resp.). An interesting outcome was the magnitude of the variable "appearance reasons to tan." A current tanned appearance therefore seemed to outweigh any adverse future appearance or health consequences caused by indoor tanning. Appearance-focused interventions to reduce such behaviour may now prove to be efficacious within a UK sample.